Model of psychological support of parents in a situation «house larceny», made by the teenager - Natalia Nikolaevna Mizina (Вестник Северо-Кавказского федерального университета)
Concepts of «house larceny» and psychological support of parents are given; psihologo-pedagogical features of detsko-parental interactions in families of the teenagers inclined to «house larceny» are considered; the tool model of psychological support of parents, its target, substantial, tool and kontrolno-estimated blocks is described.